Fermento, melaço e sulfaquinoxalina: Sua interação na alimentação dos pintos - Torres, A P (Revista Ceres, 1956)
This paper deals with the use of the yeast (by product of alcoholic fermentation from molasses), molasses and Sulfaquinoxaline in the ratio of 3, 3,1 and 0,125%, respectively, in a basal ration, in feeding chicks. 800 four-day old New Hampshire both sexes chicks in 8 groups, were used in this experiment. Alter six weeks of treatment the results were as following : without yeast, molasses and sulla 601,6 g with yeast, molasses and sulfa 600,9 g with yeast and molasses 577,4 g with yeast and sulfa 600,7 g with molasses and sulfa 594,0 g with yeast only 599,0 g with molasse only 556,3 g with sulfa only 575,2 g Higher mortality (4%) was observed when the basal ration had yeast and sulfa. The feed consumptions were practically equivalents. An analysis of variance shows significant favorable effect of the yeast (plus 12,8 g per chick) and the molasses had a detrimental effect (minus 28,4 g per head). It seems that sulfaquinoxaline lessens the detrimental effect of the molasses. Since molasses has been used largely by the mixefeeders, without any restriction, the authors suppose that it — previously mixed to bran — had some detecterious elfect in the ration. The yeast or the sulfa could control its detrimental eifect. This hypothesis could not be verilied.